Kenotariatan Reformasi Tata Kelola Majelis Pengawas Notaris untuk Mewujudkan Akuntabilitas Profesi Kenotariatan di Indonesia - Romy Agus Setiyanto (Dialogia Iuridica, 2025)
Notaries play an essential role in ensuring legal certainty through authentic deeds, yet the governance of the Supervisory Council of Notaries in Indonesia continues to face regulatory, institutional, and digitalization challenges. This study aims to formulate governance reforms to strengthen the accountability of the notarial profession. It employs a narrative review of 25 international journal articles selected through a structured process of identification, screening, and thematic analysis. The articles were examined across four thematic areas: ethics, regulation, institutional governance, and digital technology. The findings show that formal regulation alone is insufficient to guarantee accountability without the support of strong professional ethics and effective institutional mechanisms. The Supervisory Council of Notaries remains weak in terms of resources and sanction enforcement. Meanwhile, digitalization through electronic deeds, online promotion, and blockchain offers opportunities for transparency while simultaneously presenting risks to professional integrity. In conclusion, governance reform for the Supervisory Council of Notaries requires a hybrid approach that integrates ethics, regulation, institutional capacity, and technology. As recommendations, this study encourages strengthening the human resource capacity of the Supervisory Council, harmonizing regulations on electronic deeds and online promotion, and developing more transparent and independent oversight mechanisms, including the adoption of relevant technological tools. This study contributes to the literature on professional accountability in law and provides practical guidance for enhancing notarial oversight in Indonesia.